Assessing Diploma students' awareness of language learning strategies and beliefs about language learning / Johnny Ahmad - Ahmad, Johnny (2008)
This study was aimed firstly, to determine the levels of awareness among the students on language learning strategies as assessed using Oxford's Strategy Language Learning Inventory (SILL) and secondly, to determine the students' beliefs about language learning using Horwitz's Beliefs about language learning (BALLI) questionnaire. The two questionnaires were administered to a group of 35 diploma students at Universiti Teknologi MARA Sarawak, doing a Diploma in Office Management. The data collected using the two sets of questionnaires were computed and run using the SPSS 13.0 for analysis in descriptive statistics to find the mean and standard deviation. In addition, semi-structured interviews were also conducted on a group of 5 learners randomly selected from the group. The interview data was transcribed and interpreted qualitatively. The study found that the students had a very low level of usage on language learning strategies awareness. The students also demonstrated beliefs that tended to be in disagreement on two of the three sections on BALL]. The students however, showed agreement towards one section of the BALLI questionnaire. The findings indicated that the students need to be made aware of the available learning strategies in order to make them more prepared to learn language. The findings also suggested that the students be made aware of the right beliefs they need in order to be able to learn the language more effectively.